Anaesthesia for a patient with Wilson's Disease: A case report - Maharjan, SK (Journal of Kathmandu Medical College, 2014)
Wilson’s disease (WD), also known as hepatolenticular degeneration, is an autosomal recessive disorder and is due toreduction in the synthesis of copper transporter protein, Ceruloplasmin. Due to ceruloplasmin defi ciency, there is failureof excretion of copper in bile and it accumulates in body tissues leading to major hepatic and neurological involvement.Hepatic involvement after excess copper deposition leads to chronic liver disease and cirrhosis, which may altermetabolism and excretion of anaesthetic agents. The neurological effect is a movement disorder, with abnormalitiesof speech, tremor, incontinence (lack of self control) and dystonia being common features. In spite of many knownanaesthetic problems, there are very few reports of General Anaesthesia and Regional Anaesthesia in these patients, sowe report a case of Wilson`s Disease with anaesthetic management. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10552 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, page: 31-32